A PEM water electrolysis bipolar plate and preparation method thereof

By using composite plate body and plasma spraying and mold printing technology of nickel foam and titanium slurry in the production of water electrolytic bipolar plates, the problem of not being able to achieve continuous batch production in the prior art is solved, and efficient and low-cost bipolar plate production is achieved.

CN115928118BActive Publication Date: 2025-04-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211538254.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-04-11
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

The existing water electrolytic bipolar plate production process cannot achieve continuous batch production, resulting in low production efficiency and high cost, and serious material waste.

Method used

The composite plate is made by hot pressing the foam nickel foam and titanium slurry, and a titanium layer with a flow field structure is formed through plasma spraying and mold printing technology to achieve continuous production of bipolar plates.

Benefits of technology

It realizes efficient and low-cost continuous production of bipolar plates, improving production efficiency and product airtightness and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003976140470000011
    Figure HDA0003976140470000011
  • Figure HDA0003976140470000012
    Figure HDA0003976140470000012
  • Figure HDA0003976140470000021
    Figure HDA0003976140470000021
Patent Text Reader

Abstract

The present invention discloses a PEM water electrolysis bipolar plate and a preparation method, which belongs to the field of water electrolysis hydrogen production. It comprises a metal composite plate body, which is composed of nickel foam and titanium-containing slurry, wherein the titanium-containing slurry is filled inside the nickel foam, and the outer surface of the nickel foam is coated with a titanium-containing material layer formed by the titanium-containing slurry; spherical dehydrogenated titanium powder layers are arranged on the upper and lower surfaces of the metal composite plate body, and a functional coating is arranged on the spherical dehydrogenated titanium powder layer on one side, and the functional coating forms the flow field structure of the bipolar plate; the titanium-containing slurry and the functional coating contain spherical atomized titanium powder. The PEM water electrolysis bipolar plate has excellent thermal conductivity, electrical conductivity, and corrosion resistance, and the plate body is lighter, which meets the working requirements of the water electrolysis bipolar plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of hydrogen production by water electrolysis, and specifically relates to a PEM water electrolysis bipolar plate and a preparation method thereof. Background Art

[0002] As the whole society pays more and more attention to environmental protection, the use of hydrogen energy has gradually attracted attention. Water electrolysis hydrogen production technology is favored because it can obtain hydrogen safely and efficiently. The equipment for water electrolysis hydrogen production is an electrolyzer, which can electrolyze water into hydrogen and oxygen through electricity. Hydrogen and oxygen are located on both sides of the bipolar plate. As one of the core components of the electrolyzer, the bipolar plate directly affects the performance of the entire electrolyzer.

[0003] Bipolar plate is one of the key technologies of proton exchange membrane water electrolysis technology. The bipolar plate has a flow field structure, which includes flow channel ridges, spoiler columns, hydrogen and oxygen frames, and bridge areas. In addition, the bipolar plate also includes flow channel grooves, other spoiler areas at spoiler columns, and hydrogen and oxygen cavities. The flow channel ridges, flow channel grooves, hydrogen and oxygen frames, bridge areas, and spoiler areas containing spoiler columns form the flow field structure of the bipolar plate. It has the functions of support, gas isolation, conduction and heat dissipation in the hydropower digester. Therefore, there are high requirements for the mechanical properties, electrical conductivity, thermal conductivity, chemical stability and cost of the bipolar plate materials. It is of great significance to study low-cost, high chemical stability, and high electrical conductivity bipolar plates. There are three commonly used bipolar plate materials: graphite materials, composite materials, and metal materials. Graphite materials are cheap and have simple processing technology, but graphite has poor mechanical properties and is easy to break under high pressure; composite materials have good chemical stability, but poor electrical conductivity, electrothermal and mechanical properties. The traditional process for preparing water electrolysis bipolar plates generally uses pure titanium or other highly conductive composite materials. The preparation cost is high and the process is complicated. It requires separate or additional processing of water electrolysis grooves, flow channels and other parts, which results in a large amount of material waste during processing. Therefore, studying how to improve the preparation cost and performance of water electrolysis bipolar plates is a top priority in the development of water electrolysis.

[0004] At present, the production process of water electrolysis bipolar plates is still at the stage of single batch or continuous preparation of processed materials, but cannot produce water electrolysis bipolar plates in continuous batches. Researching how to achieve continuous batch production of water electrolysis bipolar plates, meeting the needs of water electrolysis development, and developing continuous batch production of water electrolysis bipolar plates are important directions to solve the current rapid development and application of water electrolysis. Summary of the invention

[0005] The purpose of the present invention is to provide a PEM water electrolysis bipolar plate and a preparation method thereof, comprising a composite plate body and a functional layer, wherein the plate body is a composite plate body made by hot pressing a mixture of foamed nickel and titanium slurry, and the functional layer is a titanium layer with a flow field structure prepared by plasma spraying and mold printing. The present invention can achieve uniformity of the overall surface of the composite plate, and in the entire production line, continuous processing of the coil can be achieved, thereby avoiding the conventional complex processing of the water electrolysis bipolar plate.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions:

[0007] The present invention provides a PEM water electrolysis bipolar plate, comprising a metal composite plate body, wherein the metal composite plate body is composed of foamed nickel and titanium-containing slurry, wherein the titanium-containing slurry is filled in the foamed nickel, and the outer surface of the foamed nickel is coated with a titanium-containing material layer formed by the titanium-containing slurry; spherical dehydrogenated titanium powder layers are arranged on the upper and lower surfaces of the metal composite plate body, wherein a functional coating is arranged on the spherical dehydrogenated titanium powder on one side, and the functional coating forms a flow field structure of the bipolar plate; the titanium-containing slurry and the functional coating contain spherical atomized titanium powder.

[0008] Furthermore, the particle size of the spherical atomized titanium powder is 20-50 μm; the particle size of the spherical dehydrogenated titanium powder is 30-100 μm; the spherical dehydrogenated titanium powder layer contains micropores, and the pore size of the micropores is 100 nm-10 μm. The micropores are obtained by controlling parameters such as flow rate, frequency, and number during the preparation process and combining the particle size control of the spherical dehydrogenated titanium powder, and are finally measured by precision measuring instruments such as microscopes.

[0009] Furthermore, the thickness of the nickel foam is 2-4 mm, the pore size is 0.1 mm-10 mm, the porosity is 50%-98%, the through-porosity is ≥98%, and the volume density is 0.1-0.8 g / cm 3 The thickness of the titanium-containing slurry layer on the outer surface of the nickel foam is 0.5-1 mm; the thickness of the spherical dehydrogenated titanium powder layer is 0.1-0.3 mm, and the thickness of the functional coating is 0.2-0.5 mm.

[0010] The present invention also provides a method for preparing a PEM water electrolysis bipolar plate, the preparation method comprising the following steps:

[0011] (1) Preparation of a metal composite plate: filling the interior of the nickel foam with a titanium-containing slurry and coating the outer surface of the nickel foam to uniformly cover it; then drying and hot pressing to obtain a metal composite plate;

[0012] (2) using plasma spraying to evenly spray spherical dehydrogenated titanium powder onto the surface of the metal composite plate to form a spherical dehydrogenated titanium powder layer;

[0013] (3) The functional coating slurry is printed onto the spherical dehydrogenated titanium powder layer by mold printing to form a flow field structure; the flow field structure described here is a broad flow field structure, including but not limited to the flow field reaction zone (flow channel ridges and flow to grooves), for example, it also includes the inlet and outlet frames of the bipolar plate, the sealing frame (hydrogen and oxygen frame), the flow field distribution area, the bridge area, or the spoiler area. Those skilled in the art can form various structures by mold printing according to actual needs.

[0014] (4) Drying and demoulding to obtain a PEM water electrolysis bipolar plate.

[0015] The present invention also provides a continuous production line for preparing the PEM water electrolysis bipolar plate, the production line having a transmission mechanism, the transmission mechanism comprising a plurality of transmission rollers for tensioning and installing the nickel foam coil to realize transmission, and unwinding rollers and winding rollers respectively installed at the head and the tail, and along the transmission direction of the transmission mechanism, unwinding rollers, a cleaning area, a drying area I, a material injection area, a drying area II, a hot pressing area, a spraying area, a cutting area, a printing area, a drying area III and a winding roller are sequentially arranged;

[0016] The injection area is provided with multiple groups of injection pipes, the hot pressing area is provided with multiple groups of pressure rollers, the spraying area is provided with multiple groups of plasma nozzles, the cutting area is provided with multiple groups of cutting rollers, the printing area is provided with a conveyor belt mechanism, and along the conveying direction of the conveyor belt mechanism, a manual position, a printing platform and a scraper are provided in sequence;

[0017] The injection pipe, pressure roller, plasma nozzle and cutting roller are all symmetrically distributed above and below the foam nickel coil.

[0018] The present invention also provides a method for batch preparing PEM water electrolysis bipolar plates using the production line, comprising the following steps:

[0019] 1) The nickel foam coil is tensioned and placed in a transmission mechanism for transmission;

[0020] 2) The nickel foam coil is cleaned in the cleaning area and dried in the drying area I, and then enters the injection area;

[0021] 3) The plurality of injection pipes work in sequence, firstly filling the titanium-containing slurry into the interior of the nickel foam, then coating the titanium-containing slurry to cover the surface of the nickel foam, and then entering the drying zone II for drying;

[0022] 4) After drying, the nickel foam coil with titanium-containing slurry is uniformly and continuously extruded into a hot pressing zone by a pressure roller to obtain a metal composite plate;

[0023] 5) The metal composite plate enters the spraying area, and the spherical dehydrogenated titanium powder is sprayed onto the upper and lower surfaces of the metal composite plate through a plasma nozzle to form a spherical dehydrogenated titanium powder layer;

[0024] 6) The metal composite plate body with the spherical dehydrogenated titanium powder layer enters the cutting zone, and is cut by the cutting roller to obtain a metal composite plate body with a hydrogen cavity and an oxygen cavity;

[0025] 7) The cut metal composite board enters the printing area. In the manual position, the mold is placed on the surface of the metal composite board. Only then is it conveyed to the printing platform. The loading area of ​​the printing platform injects the functional coating slurry onto the mold. Finally, under the action of the scraper, the functional coating slurry is printed on the surface of the metal composite board to form a functional coating;

[0026] 8) Enter the drying area III for drying. After the drying is completed, the mold is removed to complete the production of the PEM water electrolysis bipolar plate.

[0027] Furthermore, in step 3), the filling flow rate of the titanium-containing material slurry is 0.1-5 mL / min, and the filling time is 5 s-5 min.

[0028] Furthermore, in step 7), the contact pressure between the scraper and the metal composite plate is 0.05-0.1 MPa.

[0029] Furthermore, the titanium-containing slurry and the functional coating slurry both include: spherical atomized titanium powder, a solvent, a binder and a plasticizer; the solvent in the titanium-containing slurry and the functional coating slurry is independently at least one of ethanol, toluene or methanol, the binder in the titanium-containing slurry and the functional coating slurry is independently one or a mixture of two of polyvinyl butyral resin or acrylic resin, the plasticizer in the titanium-containing slurry and the functional coating slurry is independently one or a mixture of two or more of dioctyl phthalate, dibutyl phthalate or propylene glycol phthalate polyester, and the mass ratio of the spherical atomized titanium powder to the solvent, the binder and the plasticizer is 60-80:15-35:3-4:1-2.

[0030] Furthermore, the conditions of plasma spraying are: plasma enthalpy is 22-50 MJ / kg; spraying speed is 600-1000 mm / s; and spraying temperature is 150-200°C.

[0031] Furthermore, the drying temperature is 100-150° C. and the drying time is 3-5 min.

[0032] Furthermore, the hot pressing conditions are: pressure 4-8Mpa, holding time 120-180s, and hot pressing temperature 100-150°C.

[0033] Furthermore, the number of the injection tubes is 4-8.

[0034] Furthermore, the outer cutting blade and the inner cutting blade of the cutting zone are arranged on the roller with a height of 2-5 mm, and the depth of the corresponding lower knife roller is 2-5 mm.

[0035] In summary, the present invention has the following beneficial effects:

[0036] 1. Simple preparation. The present invention fills titanium with high stability on nickel foam with high conductivity. Due to the physical properties of nickel foam, it is relatively fluffy, and the titanium-containing slurry can better adhere to its interior. After filling the titanium-containing slurry, it is dried and hot-pressed to form a composite plate body with high conductivity and durability. Then, a spherical dehydrogenated titanium powder layer is sprayed with plasma, and a mold is integrated with the printed functional coating to form the flow field and the sealant wire groove and other parts, and no welding and sealing are required. Different from the traditional preparation process, the partition plate and the hydrogen and oxygen frame need to be machined separately, and then glued together to realize the assembly of the bipolar plate. In this way, due to the presence of glue, the bonding strength and integrity will affect the resistance and air tightness of the bipolar plate. The preparation process of the present invention is simpler, which improves the air tightness of the bipolar plate, improves production efficiency, and saves costs.

[0037] 2. Stable performance: Most of the traditional water electrolysis bipolar plates are made of pure titanium, which has high stability and conductivity, but the cost is relatively high. If a low-priced metal stainless steel plate is used, it is necessary to coat its surface to meet the requirements of the water electrolysis plate operation. However, even so, due to the instability of the stainless steel plate body, its durability and conductivity will decrease with long-term operation. The present invention fills the inside of the nickel foam and covers the surface with a titanium-containing slurry, which is then dried and hot-pressed to achieve a compact state, thereby avoiding gas leakage from the plate body and saving material costs. Secondly, due to the stability of the nickel material, the composite plate body formed after filling with a more stable titanium slurry is more stable, and the conductivity will be higher than that of the traditional bipolar plate. Moreover, since the prepared materials all use nickel and titanium with higher stability, the surface of the nickel foam is coated with titanium, and titanium is filled inside the nickel foam during the preparation process. The two materials are bonded by an adhesive, which will not cause the separation of the two materials due to long-term operation, and the influence of the nickel element on the water electrolyzer will not occur, thereby ensuring the efficient and stable operation of the water electrolyzer.

[0038] 3. Stable structure: A layer of spherical dehydrogenated titanium powder is sprayed on the surface of the composite plate by plasma spraying. Since the high temperature that can melt the surface particles is generated during the plasma spraying process, the particles on the surface of the composite plate will be bombarded. At this time, the titanium particles are sprayed again, which can effectively make the titanium particles penetrate into the surface of the composite plate, and the titanium particles are more densely distributed. First, the bonding force between the composite plate and the spherical dehydrogenated titanium powder layer is increased, and a solid foundation layer is laid. Then, the functional coating is printed on the surface of the spherical dehydrogenated titanium powder layer. Due to the presence of micropores in the spherical dehydrogenated titanium powder layer, combined with the influence of printing pressure, the mutual penetration of titanium particles between the functional coating and the spherical dehydrogenated titanium powder layer can be effectively enhanced, thereby improving the bonding force between the two, that is, effectively increasing the bonding force between the overall functional layer and the composite plate. That is, the present invention adopts the method of plasma spraying and mold printing superposition to prepare a titanium layer on a low-cost substrate material, which can effectively improve the conductivity and corrosion resistance of the bipolar plate and meet the operating conditions of water electrolysis.

[0039] 4. The present invention fills titanium slurry on the surface and inside of nickel foam, and performs drying and hot pressing. However, due to the characteristics of the material of nickel foam itself, it is relatively loose. After hot pressing, it is impossible to ensure that the titanium slurry completely covers or wraps the nickel foam. If the nickel foam is exposed, after a long period of operation, especially in a water environment, a dense oxide film will be generated on the surface of the nickel foam, affecting the conductivity of the bipolar plate. Therefore, on this basis, the present invention sprays a spherical dehydrogenated titanium powder layer on the surface of the composite plate through plasma, which further ensures the full coverage of titanium and avoids the problem of low durability caused by the exposure of nickel foam. Therefore, the bipolar plate prepared by the present invention has excellent durability.

[0040] 5. Efficient and fast: In the production line disclosed in the present invention, direct processing of coils is adopted. The front end uses an unwinding roller. It only needs to put the foam nickel coil in. It can be automatically operated according to the transmission mechanism, and finally completed by the winding roller. During the process, it automatically passes through the cleaning area and multiple drying areas. In the process of operation, the foam nickel is automatically injected and filled, and then passes through the hot pressing area. Under the action of the pressure roller, the uniformity of the overall surface of the composite plate can be achieved. In the whole production line, continuous processing of the coil can be achieved, avoiding the conventional complex processing of the water electrolysis bipolar plate. The conventional processing method requires the separate processing of the hydrogen and oxygen frame and the partition plate of the water electrolysis plate, and then processing and welding. Moreover, they are all single-piece processing, the process is complicated, and it affects the production efficiency, which is not conducive to the development of the water electrolysis industry. The preparation process of the present invention avoids some problems of conventional processing, and can efficiently and quickly prepare high-quality water electrolysis bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0042] Figure 1 Schematic diagram of the overall structure of the customized mold for the metal bipolar plate in an embodiment of the present invention.

[0043] Figure 2 This is a schematic diagram of the placement of the capillary when printing the functional coating.

[0044] Figure 3 This is a schematic diagram of a metal bipolar plate after printing with a custom mold.

[0045] Figure 4 This is a cross-sectional view of a metal bipolar plate after printing with a custom mold.

[0046] Figure 5 It is a schematic diagram of the batch production line of Example 4 of the present invention.

[0047] Figure 6 It is a schematic diagram of the cutting roller structure.

[0048] In the figure: 1, hollow area; 2, closed area; 3, capillary; 4, hydrogen and oxygen cavity; 4-1 hydrogen and oxygen frame; 5, flow channel groove; 6, flow channel ridge; 7, spoiler area; 7-1, spoiler column; 8, material inlet and outlet hole; 9, functional coating; 10, spherical dehydrogenated titanium powder layer; 11, composite plate body; 12, unwinding roller; 13, cleaning area; 14, drying area I; 15, injection area; 15-1, injection pipe; 16, drying area II; 17, hot pressing area; 17-1, pressure roller; 18, spraying area; 18-1, plasma nozzle; 19, cutting area; 19-1, cutting roller; 19-2, outer blade; 19-3, inner blade; 20, printing area; 20-1, manual position; 20-2, printing platform; 20-3, scraper; 21, drying area III; 22, transmission roller; 23, winding roller. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0050] Example 1

[0051] Slurry preparation: weigh 60g of spherical atomized titanium powder with a particle size of 20μm (the spherical atomized titanium powder obtained by atomization treatment can be prepared by a general method in the art), 35g of anhydrous ethanol, 4g of polyvinyl butyral resin, and 1g of dioctyl phthalate in a beaker, and stir evenly with a mechanical stirrer for later use.

[0052] Cut a piece of nickel foam with a thickness of 2mm and an area of ​​20cm x 10cm. The pore size of the nickel foam is 0.1mm, the porosity is 50%, the through-porosity is ≥98%, and the volume density is 0.1g / cm 3 . Ultrasonic cleaning with deionized water was performed for 3 times, each time for 10 minutes, and then taken out and blown dry. The slurry was evenly filled into the interior of the nickel foam and coated on its outer surface to form a titanium-containing slurry layer, and then placed in a 150°C oven for heat treatment for 3 minutes. After the time was up, it was taken out and the nickel foam was placed on the hot press platform for hot pressing to form a composite plate body 11 (the thickness of the titanium-containing slurry layer formed on the surface of the composite plate body 11 was 1 mm). The hot press platform pressure was 4 MPa, the holding time was 120 seconds, and the hot pressing temperature was 100°C. After hot pressing, the composite plate body 11 is placed on a plasma spraying platform, and the spraying machine conditions are set to a plasma enthalpy of 22 MJ / kg; a spraying speed of 600 mm / s; a spraying temperature of 150°C, and a spherical dehydrogenated titanium powder with a particle size of 30 μm (the spherical dehydrogenated titanium powder obtained by dehydrogenation treatment can be prepared by a general method in the art) is sprayed onto the surface of the composite plate body 11 to generate a spherical dehydrogenated titanium powder layer 10 with a thickness of 0.1 mm, and then a plurality of capillaries 3 are placed in parallel on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent flow zone 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the shape of the mold to form a functional coating 9; the customized mold includes a hollow area 1 and a closed area 2, the hollow area 1 is for the slurry to pass through to form the required bipolar plate structure, that is, it corresponds to the flow channel ridge 6 of the bipolar plate, the spoiler column 7-1 and the hydrogen and oxygen frame 4-1 (the hydrogen and oxygen frame 4-1 is the peripheral frame of the hydrogen and oxygen cavity 4 and the sealant wire groove part of the periphery of the bipolar plate that needs to be sealed), the closed area 2 is to block the bipolar plate where no structure needs to be formed, that is, it corresponds to the flow channel groove 5 of the bipolar plate, the spoiler area 7 except the spoiler column 7-1 and the hydrogen and oxygen cavity 4 (for hydrogen and oxygen to enter and exit the bipolar plate respectively) reserved area, etc., as shown Figure 1 and 3 As shown; the above-mentioned thin tube 3 corresponds to the position of the hollow area 1 of the customized mold to allow the slurry to pass through the printing, and form a material inlet and outlet hole 8 between the hydrogen and oxygen cavity and the turbulent area under printing, which can allow hydrogen to enter from the hydrogen and oxygen cavity and enter the flow field after passing through the thin hole, and flow out from the flow field to the hydrogen and oxygen cavity at the outlet end, that is, the bridge area, as shown Figure 2 and 4 As shown, the thickness of the customized mold is 0.3 mm (that is, the thickness of the corresponding printed functional coating 9 is 0.3 mm), and then it is placed in a 100° C. oven for heat treatment for 5 minutes. After the time is up, the mold is removed and the capillary 3 is taken out to prepare a water electrolysis bipolar plate.

[0053] In this embodiment, a composite plate with high conductivity is generated by hot pressing of nickel foam and titanium-containing slurry, and a water electrolysis bipolar plate is prepared by plasma spraying and mold printing. After testing, the contact resistance of the prepared bipolar plate is only 0.41 mΩ·cm 2 , the corrosion current density is 2.17μA / cm 2 .

[0054] Example 2

[0055] Preparation of slurry: weigh 70 g of spherical atomized titanium powder with a particle size of 35 μm, 20 g of anhydrous ethanol, 3.5 g of polyvinyl butyral resin, and 1.5 g of dioctyl phthalate in a beaker, and stir evenly with a mechanical stirrer for later use.

[0056] Cut a piece of nickel foam with a thickness of 3mm and an area of ​​20cm x 10cm. The pore size of the nickel foam is 10mm, the porosity is 98%, the through-porosity is ≥98%, and the volume density is 0.8g / cm 3 . Ultrasonic cleaning with deionized water was performed for 3 times, each time for 10 minutes, and then taken out and blown dry. The slurry was evenly filled into the interior of the nickel foam and coated on its outer surface to form a titanium-containing slurry layer, and then placed in a 130°C oven for heat treatment for 4 minutes. After the time was up, it was taken out and the nickel foam was placed on the hot press platform for hot pressing to form a composite plate body 11 (the thickness of the titanium-containing slurry layer formed on the surface of the composite plate body 11 was 1 mm). The hot press platform pressure was 4 MPa, the holding time was 150 seconds, and the hot pressing temperature was 100°C. After hot pressing, the composite plate body 11 is placed on the plasma spraying platform, and the spraying machine conditions are set to a plasma enthalpy of 36 MJ / kg; a spraying speed of 800 mm / s; and a spraying temperature of 175°C. Spherical dehydrogenated titanium powder with a particle size of 60 μm is sprayed onto the surface of the composite plate body 11 to generate a spherical dehydrogenated titanium powder layer 10 with a thickness of 0.3 mm. Subsequently, a plurality of capillaries 3 are placed in parallel on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent flow zone 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the shape of the mold to form a functional coating 9. The structure of the customized mold is the same as that of Example 1, and the thickness of the customized mold is 0.4 mm (i.e., the thickness of the corresponding printed functional coating 9 is 0.4 mm). It is then placed in a 125°C oven for heat treatment for 4 minutes, and after the time is up, the mold is removed and the capillary 3 is removed to prepare a water electrolysis bipolar plate.

[0057] After testing, the contact resistance of the water electrolysis bipolar plate prepared in this embodiment is 0.43mΩ·cm 2 , the corrosion current density is 2.21μA / cm2 , reflecting its ultra-high performance output and ultra-long durability.

[0058] Example 3

[0059] Preparation of slurry: weigh 80 g of spherical atomized titanium powder with a particle size of 50 μm, 15 g of anhydrous ethanol, 3 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir them evenly with a mechanical stirrer for later use.

[0060] Cut a piece of nickel foam with a thickness of 4mm and an area of ​​20cm x 10cm. The pore size of the nickel foam is 10mm, the porosity is 98%, the through-porosity is ≥98%, and the volume density is 0.8g / cm 3 . Ultrasonic cleaning with deionized water was performed for 3 times, each time for 10 minutes, and then taken out and blown dry. The slurry was evenly filled into the interior of the nickel foam and coated on its outer surface to form a titanium-containing slurry layer, and then placed in a 100°C oven for heat treatment for 5 minutes. After the time was up, it was taken out and the nickel foam was placed on the hot press platform for hot pressing to form a composite plate body 11 (the thickness of the titanium-containing slurry layer formed on the surface of the composite plate body 11 was 1 mm). The hot press platform pressure was 4 MPa, the holding time was 180 seconds, and the hot pressing temperature was 120°C. After hot pressing, the composite plate body 11 is placed on the plasma spraying platform, and the spraying machine conditions are set to a plasma enthalpy of 50MJ / kg; a spraying speed of 1000mm / s; a spraying temperature of 200°C, and spherical dehydrogenated titanium powder with a particle size of 100μm is sprayed onto the surface of the composite plate body 11 to generate a spherical dehydrogenated titanium powder layer 10 with a thickness of 0.2mm. Subsequently, a plurality of capillaries 3 are placed in parallel on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent flow zone 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the shape of the mold to form a functional coating 9. The structure of the customized mold is the same as that of Example 1, and the thickness of the customized mold is 0.5 mm (i.e., the thickness of the corresponding printed functional coating 9 is 0.5 mm). It is then placed in a 150°C oven for heat treatment for 3 minutes. After the time is up, the mold is removed and the capillary 3 is removed to prepare a water electrolysis bipolar plate.

[0061] The prepared bipolar plate has high performance and high durability. The specific data are shown in Table 1. It can be seen that the contact resistance of the bipolar plate is 0.42mΩ·cm 2 , the corrosion current density is 2.19μA / cm 2 .

[0062] Comparative Example 1

[0063] Preparation of slurry: weigh 60 g of spherical atomized titanium powder with a particle size of 20 μm, 35 g of anhydrous ethanol, 4 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir them evenly with a mechanical stirrer for later use.

[0064] A stainless steel plate with a thickness of 1 mm and an area of ​​20 cm x 10 cm was cut as the substrate, and polished step by step using 200-500 mesh sandpaper. The plate was then ultrasonically cleaned in an acetone solution for 3 times, each time for 10 min. After cleaning, it was rinsed with ultrapure water and then taken out and blown dry.

[0065] The cleaned stainless steel plate is placed on the plasma spraying platform, and the spraying machine conditions are set to plasma enthalpy of 22MJ / kg; spraying speed of 600mm / s; spraying temperature of 150°C, and spherical dehydrogenated titanium powder with a particle size of 30μm is sprayed onto the stainless steel surface. Then, multiple capillaries 3 are placed in parallel on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent flow area 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold plate is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the mold shape to form a functional coating 9; the customized mold structure is the same as in Example 1, and the thickness of the customized mold is 0.3 mm. It is then placed in a 100°C oven for heat treatment for 5 minutes. After the time is up, the mold is removed and the capillary 3 is taken out to prepare a water electrolysis bipolar plate.

[0066] In this comparative example, a titanium functional layer is prepared on both sides of the stainless steel by plasma spraying and mold printing to cover the stainless steel surface. The prepared bipolar plate has a lower contact resistance. However, since the plate body itself is still made of stainless steel, its corrosion resistance is still somewhat lower than that of nickel and titanium, and it cannot be mass-produced, resulting in a waste of manpower and material resources. As shown in Table 1, its corrosion current density is 3.25μA / cm 2 .

[0067] Comparative Example 2

[0068] Preparation of slurry: weigh 60 g of spherical atomized titanium powder with a particle size of 20 μm, 35 g of anhydrous ethanol, 4 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir them evenly with a mechanical stirrer for later use.

[0069] Cut a piece of nickel foam with a thickness of 2mm and an area of ​​20cm x 10cm. The pore size of the nickel foam is 0.1mm, the porosity is 50%, the through-porosity is ≥98%, and the volume density is 0.1g / cm 3. And use deionized water to ultrasonically clean it 3 times, each time for 10 minutes, and then take it out and blow it dry. The slurry is evenly filled into the interior of the nickel foam and coated on its outer surface to form a titanium-containing slurry layer, and then placed in a 150°C oven for heat treatment for 3 minutes. After the time is up, take it out and place the nickel foam on the hot press platform for hot pressing to form a composite plate body 11 (the thickness of the titanium-containing slurry layer formed on the surface of the composite plate body 11 is 1 mm), the hot press platform pressure is 4 MPa, and the holding time is 120 seconds. After hot pressing, multiple capillaries 3 are placed in parallel on the surface of the composite plate 11, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulence zone 7. Then, the customized mold plate is placed in parallel on the front surface of the composite plate, and the slurry is printed on the composite plate 11 along the shape of the mold to form a functional coating 9. The customized mold structure is the same as that in Example 1, and the thickness of the customized mold is 0.3 mm. Then, it is placed in a 100°C oven for heat treatment for 5 minutes. After the time is up, the mold is removed and the capillaries 3 are removed to prepare a water electrolysis bipolar plate.

[0070] Although the composite material plate was prepared by mixing nickel foam and titanium-containing slurry, the plate was not plasma sprayed after hot pressing. As a result, when the mold was printed, the corresponding groove of the mold could not be covered with titanium slurry, and some nickel foam was still exposed on the surface, which had a certain impact on its durability. At the same time, without plasma spraying of titanium powder, the bonding force between the plate and the functional coating is poor, and it is easy to fall off, which will also cause problems such as large contact resistance and high corrosion current. After testing, its corrosion current density is 7.98μA / cm 2 , more than double that of Example 1.

[0071] Table 1 Test results

[0072] Serial number <![CDATA[Contact resistance mΩ·cm 2 > <![CDATA[Corrosion current density μA / cm 2 > Example 1 0.41 2.17 Example 2 0.43 2.21 Example 3 0.42 2.19 Comparative Example 1 0.67 3.25 Comparative Example 2 0.83 7.98

[0073] Example 4

[0074] A production line for a batch preparation method of a PEM water electrolysis bipolar plate, such as Figure 5 As shown, it includes a transmission mechanism, which includes a plurality of conveying rollers 22 for tensioning and installing the nickel foam coil to realize transmission, and an unwinding roller 12 and a winding roller 23 installed at the head and tail, and an unwinding roller 12, a cleaning area 13, a drying area I 14, a material injection area 15, a drying area II 16, a hot pressing area 17, a spraying area 18, a cutting area 19, a conveying roller 22, a printing area 20, a drying area III 21, and a winding roller 23 are sequentially arranged along the transmission direction of the transmission mechanism.

[0075] The unwinding roller 12, the conveying roller 22 and the winding roller 23 work together to realize the tensioning and continuous conveying of the coil on this production line. The cleaning area 13 includes a cleaning tank, and the drying area I 14, the drying area II 16, and the drying area III 21 all include ovens. The injection area 15 is provided with a plurality of groups of injection pipes 15-1 that can discharge materials evenly. In this embodiment, 4 groups are set (one group is a injection pipe), which are symmetrically distributed in pairs above and below the coil, that is, two groups of injection pipes 15-1 are provided above the coil, and two groups of injection pipes 15-1 are also provided below the coil.

[0076] The hot pressing zone 17 is provided with two upper and lower pressure rollers 17-1 which are meshed with each other and continuously run and apply a preset uniform pressure to the coil. The spraying zone 18 is provided with a plurality of plasma nozzles 18-1. The cutting zone 19 is provided with two upper and lower cutting rollers 19-1 which are meshed with each other and continuously drive and cut. The cutting roller 19-1 has an outer cutting blade 19-2 and an inner cutting blade 19-3. Figure 6 As shown, the outer cutting blade 19-2 realizes frame-type cutting of the coil to form a plate piece, and the inner blade 19-3 simultaneously cuts the coil to form the hydrogen and oxygen cavity structure of the bipolar plate. The printing area 20 is provided with a manual position 20-1 and a printing platform 20-2. The manual position 20-1 contains a customized mold and a capillary, and the printing platform 20-2 is provided with a loading area and a scraper 20-3. The injection tube 15-1, the pressure roller 17-1, the plasma nozzle 18-1, and the cutting roller 19-1 are all symmetrically arranged with the coil connected to the unwinding roller 12 and the winding roller 22, and the upper and lower numbers are the same and the positions are corresponding.

[0077] The customized mold includes a hollow area 1 and a closed area 2. The hollow area 1 is for the slurry to pass through to form the required bipolar plate structure, that is, it corresponds to the flow channel ridge 6 of the bipolar plate, the spoiler column 7-1 and the hydrogen and oxygen frame 4-1 (the hydrogen and oxygen frame 4-1 is the peripheral frame of the hydrogen and oxygen cavity 4 and the sealant wire groove part of the periphery of the bipolar plate that needs to be sealed). The closed area 2 is for shielding the bipolar plate where no structure needs to be formed, that is, it corresponds to the flow channel groove 5 of the bipolar plate, the spoiler area 7 except the spoiler column 7-1 and the hydrogen and oxygen cavity 4 (for hydrogen and oxygen to enter and exit the bipolar plate respectively), etc. Figure 1 and 3 As shown; the above-mentioned capillary tube 3 corresponds to the position of the hollow area 1 of the customized mold to allow the slurry to pass through the printing, and form a material inlet and outlet hole 8 between the hydrogen and oxygen cavity and the turbulent area under printing, which can allow hydrogen to enter from the hydrogen and oxygen cavity and enter the flow field after passing through the capillary hole, and flow out from the flow field to the hydrogen and oxygen cavity at the outlet end, as shown Figure 2 and 4 shown.

[0078] like Figure 5As shown, the nickel foam coil is placed in the unwinding roller 12, and a portion is stretched out to be tensioned around a plurality of transmission rollers 22, and then wound in the winding roller 23. Under the joint action of the unwinding roller 12, the transmission roller 22, and the winding roller 23, the continuous transmission of the nickel foam coil is realized. As the equipment is running, the transmission starts, and the nickel foam coil first enters the cleaning area 13. During the coil transmission process, it passes through the cleaning pool of the cleaning area 13. The deionized water in the cleaning pool realizes a comprehensive immersion cleaning of the nickel foam, removing impurities on the surface and inside of the nickel foam. As the transmission proceeds, the nickel foam is transmitted out of the cleaning area 13, and the cleaning of the nickel foam is completed.

[0079] After the foam nickel is cleaned, it enters the drying area I14 at a temperature of 120° C. for drying, and adopts a blast drying method to remove excess moisture on the surface and inside of the foam nickel.

[0080] After drying, the coil enters the injection area 15, and the injection pipe 15-1 of the injection area 15 is connected to the material box. The four injection pipes 15-1 inject titanium-containing slurry into the upper surface, lower surface and inside of the nickel foam in the injection area 15, respectively, to achieve the overall filling of the nickel foam with slurry. The four injection pipes 15-1 inject the nickel foam in layers, along the conveying direction, firstly, the first two groups of injection pipes 15-1 located symmetrically above and below the coil contact the coil and start injecting, control the filling flow rate to 2mL / min, and the injection time to 3min, to complete the filling of the liquid inside the coil, and then the last two groups of injection pipes 15-1 contact the coil and start injecting, control the filling flow rate to 2mL / min, and the injection time to 3min, to complete the injection of the surface of the coil. The production line of the present invention can modify the parameters such as the injection pressure and injection flow of the injection pipe 15-1 according to different plate requirements.

[0081] As the transmission proceeds, the nickel foam is filled and enters the drying zone II 16 at a temperature of 120°C for drying to remove the moisture in the slurry in the nickel foam. After drying, it enters the hot pressing zone 17. The hot pressing conditions are: pressure 5Mpa, holding time 100s, and hot pressing temperature 150°C. The purpose is to hot press the dried coil to make the solidified titanium slurry and nickel foam inside and on the surface reach a compact state to prevent safety hazards such as plate leakage caused by excessive gas pressure during the subsequent operation of the water electrolyzer. At the same time, due to the stronger contact force of the plate, its conductivity is improved, and the titanium slurry and nickel foam become a whole. After the hot pressing is completed, a composite plate containing nickel foam / titanium is generated in batches with high hardness and conductivity.

[0082] After the hot pressing is completed, the coiled material with the composite plate body enters the spraying area 18. At this time, the plasma nozzle 18-1 in the spraying area 18 starts to work continuously, continuously and evenly sprays the spherical dehydrogenated titanium powder to the upper and lower surfaces of the composite plate body. The spraying time is based on the time when the plate passes through the spraying area 18. From the start of spraying until the production task is completed, the spraying area 18 works continuously throughout the whole process, continuously spraying the plate to generate a spherical dehydrogenated titanium powder layer 10. After spraying, the plate body itself has been pre-treated and has high strength and high conductivity.

[0083] In the above process, in order to avoid environmental pollution or waste caused by the dripping of the material liquid on the lower surface of the coil, a collecting box can be set directly below the injection area and the spraying area.

[0084] After spraying, the composite plate with the spherical dehydrogenated titanium powder layer 10 enters the cutting zone 19. The cutting zone 19 comprises two upper and lower cutting rollers 19-1. The cutting roller 19-1 comprises an outer blade 19-2 and an inner blade 19-3. Figure 6 As shown, the outer blade 19-2 is responsible for cutting the block-shaped composite plate body 11 for water electrolysis from the long composite plate body, and the inner blade 19-3 cuts the hydrogen cavity and oxygen cavity of the water electrolysis bipolar plate. The cutting roller 19-1 rotates continuously to realize the continuous cutting of the composite plate body. After cutting the composite plate body 11 for water electrolysis, the excess waste is continued to be conveyed by the conveying roller 22 to the winding roller 23 for winding.

[0085] The cut water electrolysis size composite board 11 can be taken down manually and enter the printing area 20. A conveyor belt mechanism is also designed in the printing area 20. Along the conveying direction of the conveyor belt mechanism, an artificial area 20-1 and a printing platform 20-2 are arranged in sequence. The printing platform 20-2 includes a feeding component and a scraper 20-3 controlled by a driver to achieve up, down, left and right sliding movement. The scraper 20-3 is designed to be inclined. Driven by the driver, the scraper 20-3 makes its bottom surface contact with the slurry to achieve flattening. The staff places the composite board 11 in the artificial area and places a customized mold on the composite board 11. Then, it automatically enters the printing platform 20-2 under the conveyor belt. The feeding component sucks the material to And inject the material into the hollow area of ​​the customized mold, so that the liquid material is filled and slightly overflows the hollow area, and then it is transmitted to the scraper 20-3. The scraper 20-3 begins to press down and contact the composite plate body 11 under the action of the driver, and sets a pressure of 0.05-0.1Mpa to prevent it from deflecting and ensure that the printed slurry is compact and free of bubbles. Then, during the continued transmission of the composite plate body 11, the slurry follows the scraper 20-3 from the surface of the customized mold to fully enter the hollow area 1 to ensure that the slurry fills all corners of the composite plate body 11 along the direction of the mold, and is scraped and compacted by the scraper 20-3 to form a preliminary flow field structure. After printing is completed, the scraper 20-3 returns to its position, and the plate enters the conveyor belt to continue operation.

[0086] After printing is completed, under the action of the conveyor belt, the plate and the mold enter the drying area Ⅲ21 with a temperature of 120°C, and are dried as a whole in the drying area Ⅲ21. After drying, the mold is manually removed and the capillary is taken out. At this point, the preparation of the water electrolysis bipolar plate is completed.

[0087] This embodiment adopts a batch production line to prepare PEM water electrolysis bipolar plates. In the whole production line, continuous processing of coils can be achieved, avoiding the conventional complex processing of water electrolysis bipolar plates, and can efficiently and quickly prepare high-quality water electrolysis bipolar plates. After testing, the contact resistance of the bipolar plates prepared in this embodiment is 0.42mΩ·cm 2 , the corrosion current density is 2.14μA / cm 2 .

[0088] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A PEM water electrolysis bipolar plate, characterized in that: The invention comprises a metal composite plate body, wherein the metal composite plate body is composed of nickel foam and titanium-containing slurry, wherein the titanium-containing slurry is filled inside the nickel foam, and the outer surface of the nickel foam is coated with a titanium-containing material layer formed by the titanium-containing slurry; spherical dehydrogenated titanium powder layers are arranged on the upper and lower surfaces of the metal composite plate body, and a functional coating is arranged on the spherical dehydrogenated titanium powder layer on one side, wherein the functional coating forms a flow field structure of the bipolar plate; the titanium-containing slurry and the functional coating contain spherical atomized titanium powder; The particle size of the spherical atomized titanium powder is 20-50 μm; the particle size of the spherical dehydrogenated titanium powder is 30-100 μm; micropores are distributed in the spherical dehydrogenated titanium powder layer, and the pore size of the micropores is 100 nm-10 μm; The thickness of the nickel foam is 2-4 mm, the pore size is 0.1 mm-10 mm, the porosity is 50%-98%, the through-porosity is ≥98%, and the volume density is 0.1-0.8 g / cm 3 The thickness of the titanium-containing slurry layer on the outer surface of the nickel foam is 0.5-1 mm; the thickness of the spherical dehydrogenated titanium powder layer is 0.1-0.3 mm, and the thickness of the functional coating is 0.2-0.5 mm.

2. A method for preparing a PEM water electrolysis bipolar plate according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Preparation of a metal composite plate: filling the interior of the nickel foam with a titanium-containing slurry and coating the outer surface of the nickel foam to uniformly cover it; then drying and hot pressing to obtain a metal composite plate; (2) using plasma spraying to evenly spray spherical dehydrogenated titanium powder onto the surface of the metal composite plate to form a spherical dehydrogenated titanium powder layer; (3) printing the functional coating slurry onto the spherical dehydrogenated titanium powder layer by a mold printing method to form a flow field structure; (4) Drying and demoulding to obtain a PEM water electrolysis bipolar plate.

3. A continuous production line for preparing the PEM water electrolysis bipolar plate according to claim 1, characterized in that: The production line has a transmission mechanism, which includes a plurality of transmission rollers (22) for tensioning and installing the nickel foam coil to realize transmission, and an unwinding roller (12) and a winding roller (23) respectively installed at the head and the tail, and along the transmission direction of the transmission mechanism, the unwinding roller (12), the cleaning area (13), the drying area I (14), the injection area (15), the drying area II (16), the hot pressing area (17), the spraying area (18), the cutting area (19), the printing area (20), the drying area III (21) and the winding roller (23) are arranged in sequence; The injection area (15) is provided with a plurality of injection pipes (15-1), the hot pressing area (17) is provided with a plurality of pressure rollers (17-1), the spraying area (18) is provided with a plurality of plasma nozzles (18-1), the cutting area (19) is provided with a plurality of cutting rollers (19-1), the printing area (20) is provided with a conveyor belt mechanism, and along the conveying direction of the conveyor belt mechanism, a manual position (20-1), a printing platform (20-2) and a scraper (20-3) are provided in sequence; The injection pipe (15-1), the pressure roller (17-1), the plasma nozzle (18-1), and the cutting roller (19-1) are symmetrically distributed above and below the foam nickel coil.

4. A method for mass-producing PEM water electrolysis bipolar plates using the production line of claim 3, characterized in that: The following steps are involved: 1) The nickel foam coil is tensioned and placed in a transmission mechanism for transmission; 2) The nickel foam coil is sequentially cleaned in the cleaning area (13) and dried in the drying area I (14) before entering the injection area (15); 3) The plurality of injection pipes (15-1) work in sequence, first filling the titanium-containing slurry into the interior of the nickel foam, then coating the titanium-containing slurry to cover the surface of the nickel foam, and then entering the drying zone II (16) for drying; 4) After drying, the nickel foam coil is put into the hot pressing zone (17), and the pressure roller (17-1) uniformly and continuously extrude the nickel foam coil with the titanium-containing slurry to obtain a metal composite plate; 5) The metal composite plate enters the spraying area (18), and the spherical dehydrogenated titanium powder is sprayed onto the upper and lower surfaces of the metal composite plate through the plasma nozzle (18), forming a spherical dehydrogenated titanium powder layer; 6) The metal composite plate body with the spherical dehydrogenated titanium powder layer enters the cutting zone (19), and is cut by the cutting roller (19-1) to obtain a metal composite plate body with a hydrogen cavity and an oxygen cavity; 7) The cut metal composite plate enters the printing area (20), and in the manual position (20-1), the mold is placed on the surface of the metal composite plate, and then it is transferred to the printing platform (20-2). The loading area of ​​the printing platform (20-2) injects the functional coating slurry onto the mold, and finally, under the action of the scraper (20-3), the functional coating slurry is printed on the surface of the metal composite plate to form a functional coating; 8) Entering the drying zone III (21) for drying, after the drying is completed, the mold is removed to complete the production of the PEM water electrolysis bipolar plate.

5. The method according to claim 4, characterized in that: In step 3), the filling flow rate of the titanium-containing slurry is 0.1-5 mL / min, and the time is 5 s-5 min; in step 7), the contact pressure between the scraper (20-3) and the metal composite plate is 0.05-0.1 MPa.

6. The method according to claim 2 or 4, characterized in that: The titanium-containing slurry and the functional coating slurry both include: spherical atomized titanium powder, a solvent, a binder and a plasticizer; the solvent in the titanium-containing slurry and the functional coating slurry is independently at least one of ethanol, toluene or methanol, the binder in the titanium-containing slurry and the functional coating slurry is independently one of polyvinyl butyral resin or acrylic resin or a mixture of two, the plasticizer in the titanium-containing slurry and the functional coating slurry is independently one of dioctyl phthalate, dibutyl phthalate or propylene glycol phthalate polyester or a mixture of two or more, and the mass ratio of the spherical atomized titanium powder to the solvent, the binder and the plasticizer is 60-80:15-35:3-4:1-2.

7. The method according to claim 2 or 4, characterized in that: The conditions of plasma spraying are: plasma enthalpy is 22-50MJ / kg; spraying speed is 600-1000mm / s; spraying temperature is 150-200℃.

8. The method according to claim 2 or 4, characterized in that: The drying temperature is 100-150°C; the hot pressing conditions are: pressure 4-8Mpa, holding time 120-180s, and hot pressing temperature 100-150°C.

Citation Information

Patent Citations

  • Multi-layer composite oxygen catalyst electrode and manufacturing method thereof

    CN106374115A